Why Is the European Union Challenging Norway Over Snow Crab? Svalbard, Special Interests, and Arctic Governance. (3rd July 2019) - Østhagen, Andreas; Raspotnik, Andreas
Abstract: Why is the European Union (EU) pursuing a relatively minor issue over the right to catch snow crab in the Barents Sea? The issue has highlighted an underlying disagreement between Norway and the EU over the status of the maritime zones around the archipelago of Svalbard, stemming from the 1920 Spitsbergen Treaty. Is the EU using the snow crab to challenge Norway's Svalbard regime? The answer is that the EU is a multifaceted animal, where special interests can hijack the machinery and bring issues to the table, given the right circumstances. This article outlines these circumstances, as well as the evolution and the sources of the dispute over the snow crab, as it relates to not only economic interests, but international politics as well as law.